Factors associated with elevated blood lead concentrations in children in Karachi, Pakistan - Rahbar Mohammad Hossein; White Franklin; Agboatwalla Mubina; Hozhabri Siroos; Luby Stephen (The World Health Organization, 2002)
OBJECTIVES: To confirm whether blood lead concentrations in Karachi were as high as reported in 1989 and to identify which types of exposure to lead contribute most to elevated blood lead concentrations in children in Karachi. METHODS: A total of 430 children aged 36-60 months were selected through a geographically stratified design from the city centre, two suburbs, a rural community and an island situated within the harbour at Karachi. Blood samples were collected from children and a pretested questionnaire was administered to assess the effect of various types of exposure. Cooked food, drinking-water and house dust samples were collected from households. FINDINGS: About 80% of children had blood lead concentrations 10 µg/dl, with an overall mean of 15.6 µg/dl. At the 5% level of significance, houses nearer to the main intersection in the city centre, application of surma to children's eyes, father's exposure to lead at workplace, parents' illiteracy and child's habit of hand- to-mouth activity were among variables associated with elevated lead concentrations in blood. CONCLUSION: These findings are of public health concern, as most children in Karachi are likely to suffer some degree of intellectual impairment as a result of environmental lead exposure. We believe that there is enough evidence of the continuing problem of lead in petrol to prompt the petroleum industry to take action. The evidence also shows the need for appropriate interventions in reducing the burden due to other factors associated with this toxic element.